2010
DOI: 10.1097/pec.0b013e3181ef0473
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal View of Resident Education in Pediatric Emergency Interhospital Transport

Abstract: : The educational structure for residents serving in pediatric emergency interhospital transport teams remains variable, and the full educational value of pediatric transports continues to be somewhat unrealized particularly in the area of posttransport performance feedback and evaluation. Having medical command available has consistently been a strong point of the residents' experience on the transport team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Our study confirms findings from previous studies regarding variable exposure to transport medicine for pediatric residents [57]. This study shows that there is broad agreement that Transport Physiology, Principles of Medical Control and Medical Protocols are of higher priority than Vehicle Safety, State and Federal Regulations or Medicolegal Issues.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study confirms findings from previous studies regarding variable exposure to transport medicine for pediatric residents [57]. This study shows that there is broad agreement that Transport Physiology, Principles of Medical Control and Medical Protocols are of higher priority than Vehicle Safety, State and Federal Regulations or Medicolegal Issues.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies demonstrate participation in Emergency Medical Services or pediatric transport teams occurs in just 60% of pediatric residencies, with variable team roles and experiences at those programs [57]. It is clear that pediatric residents do not receive uniform exposure to transport medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies have shown that the educational structure of interhospital transport team has been the strong point for successful of transportation. [10][11][12][13] We suggest that the transport teams should be trained for core concepts in pediatric transport. The teams should be able to perform emergency procedure such as ET tube intubation, defibrillation, and cardiopulmonary resuscitation.…”
Section: Personnelmentioning
confidence: 99%
“…17,[19][20][21] Multiple modalities are used in continuing education programs, including quality improvement initiatives, didactics, skills laboratories, case conferences, case simulations, literature/practice reviews, computer-based activities, and peer performance. Coupling continuing education with competency assessments allows programs to provide individual support while maintaining overall performance standards.…”
Section: Training Simulation Safety and Work Hours Trainingmentioning
confidence: 99%